Optimizing Plastic Waste Reduction through Education and Ecobrick Implementation in Penjalin Village - Shanti Laila Najmia; Selvia Wulandari; Rahma Shofa Salsabila (Lembaga Pengembangan Kinerja Dosen, 2024)
This study investigates the implementation of ecobricks as a strategy to reduce plastic waste in Penjalin Village. The research focused on the effectiveness of educational workshops and community involvement in promoting sustainable waste management practices. Data was collected through surveys, interviews, workshops, and observations conducted over three months. The results showed that plastic waste is a significant issue in the village, with limited awareness of proper waste disposal methods. The introduction of ecobricks, coupled with community education, resulted in increased participation and a positive shift in attitudes towards environmental sustainability. The study also found that the success of the ecobrick initiative relies heavily on continued education and community engagement. The findings suggest that similar strategies could be effective in other rural areas facing similar challenges. This research contributes to the broader discourse on sustainable waste management and highlights the potential of ecobricks as a practical solution to plastic waste problems.